ACTH-Modulated Membrane Guanylate Cyclase Signaling System: Origin and Creation - Sharma, Rameshwar K. (Frontiers in Molecular Neuroscience, 2022)
CONSTITUTED OF SEVEN SIGNALING PATHWAYS, THE MEMBRANE GUANYLATE CYCLASE (MGC) CELLUAR SIGNALING PATHWAY is critical for the survival of Prokaryote, Eukaryote and highly complex vertebrate organisms. A sequel to the author’s earlier comprehensive reviews, covering the field of MGC from the origin to its establishment to the year 2015, this article exclusively deals with the history of its development from the year 1963 up to 1987. It narrates the efforts involved in building on small projects, brick by brick, and its emergence from the chasm of disbelief, through steady, continuous work. To make the presentation simple and chronologically continuous, the subject matters of the earlier reviews (Sharma and Duda, 1997; Pugh et al., 1997; Sharma, 2002; Duda et al., 2005; Sharma, 2010; Sharma and Duda, 2012, Duda and Sharma, 2014) and publication of these authors have been freely borrowed with appropriate citations.